2017
DOI: 10.1002/jsfa.8673
|View full text |Cite|
|
Sign up to set email alerts
|

Application of power ultrasound on the convective drying of fruits and vegetables: effects on quality

Abstract: Drying gives rise to products with a long shelf life by reducing the water activity to a level that is sufficiently low to inhibit the growth of microorganisms, enzymatic reactions and other deteriorative reactions. Despite the benefits of this operation, the quality of heat sensitive products is diminished when high temperatures are used. The use of low drying temperatures reduces the heat damage but, because of a longer drying time, oxidation reactions occur and a reduction of the quality is also observed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 84 publications
(248 reference statements)
1
50
0
10
Order By: Relevance
“…On the other hand, the cavitation effect could generate enormous tiny cavities with violent kinetic energy and compression energy inside potato tissue (Liu, Zeng, Hu, & Sun, 2020; Sun, Liu, et al, 2017). Similar phenomenon was observed in other studies (Liu, Zeng, Wang, Sun, & Xi, 2019; Rodiuguez et al, 2018). García‐Pérez, Carcel, Riera, and Mulet (2009) also stated that the application of ultrasound enhanced the effective water diffusion coefficient and the D eff is linearly proportional to ultrasonic power.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, the cavitation effect could generate enormous tiny cavities with violent kinetic energy and compression energy inside potato tissue (Liu, Zeng, Hu, & Sun, 2020; Sun, Liu, et al, 2017). Similar phenomenon was observed in other studies (Liu, Zeng, Wang, Sun, & Xi, 2019; Rodiuguez et al, 2018). García‐Pérez, Carcel, Riera, and Mulet (2009) also stated that the application of ultrasound enhanced the effective water diffusion coefficient and the D eff is linearly proportional to ultrasonic power.…”
Section: Resultssupporting
confidence: 91%
“…From the figures obtained for the diffusion coefficient and the mass transfer coefficient, it could be concluded that the use of acoustic energy contributed to the acceleration of the drying process, not only decreasing the external resistance but also increasing the water mobility inside the food. The mechanical vibration produced by the ultrasound application affected both the internal resistance to the mass transport, by successive compressions and expansions of the material (‘sponge effect’), and the external resistance to the mass transport due to the reduction of the boundary layer, which eased the vapor transfer rate from the solid surface to the drying air . The sum of both effects led to an improvement in the water release during the drying process.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical vibration produced by the ultrasound application affected both the internal resistance to the mass transport, by successive compressions and expansions of the material ('sponge effect'), and the external resistance to the mass transport due to the reduction of the boundary layer, which eased the vapor transfer rate from the solid surface to the drying air. 29 The sum of both effects led to an improvement in the water release during the drying process.…”
Section: Diffusion Modelmentioning
confidence: 99%
“…Literature data indicate that, depending on the cultivar, the anthocyanin content in ready-to-eat dried sour cherry snacks can range from 80 to as much as 320 mg of anthocyanins in 100 grams of product (Konopacka & Mieszczakowska-Frąc 2014). Also the choice of modern drying techniques, such as microwaves or ultrasound, can reduce the drying time or lower the process temperature, and thus contribute to better preservation of bioactive ingredients in the dried product (Wojdyło et al 2014b;Calín-Sánchez 2015;Fan et al 2017;Figiel & Michalska 2017;Horuz et al 2017;Onwude et al 2017;Rodríguez et al 2017). As the application of the microwave technique for drying of perishable fruits has been confirmed to be highly effective (Michalska et al 2016;Zielinska & Michalska 2016), the application of ultrasound in drying processes still remains at the experimental stage (Konopacka et al 2015a).…”
Section: ____________________________________________________________mentioning
confidence: 99%